The Love of the Qur'an Culture Program in Forming the Islamic Character of Elementary School Students - Fatmawati, Fatmawati; Amaliah, Resky (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Religious character formation in elementary school pupils commonly suffers moral degeneration in the digital age; therefore, habituation in schools is needed to strengthen religious ideals. Elementary School 266 Pakkanna started a specific program to address this issue; however, its efficacy and implementation challenges need further study. This study examines the Culture of Love for the Qur'an program, its impact on students' Islamic character, and supporting and limiting elements. This study is descriptive and qualitative. Field observations and in-depth interviews with Elementary School 266 Pakkanna's principal and teachers collected data. To verify the findings, qualitative descriptions and data triangulation were used. The study found that 1) joint tadarus activities before class, tahsin classes for grades 1–3, and a tahfidz program using memorization cards for grades 4–6 are used to implement the program; 2) this program helps students become faithful and pious by internalizing Qur'an values; and 3) student motivation and teacher-parent collaboration are key. This study helps educators incorporate Al-Qur'anic ideals into school culture and strengthens elementary school religion-based character education management research.